Ox40-Cre–mediated deletion of BRD4 reveals an unexpected phenotype of hair follicle stem cells in alopecia - Mou Wen; Yuanlin Ying; Xiang Xiao; Preston R. Arnold; Guangchuan Wang; Xiufeng Chu; Rafik M. Ghobrial; Xian C. Li (JCI Insight, 2022)
BRD4 is a bromodomain extraterminal domain family member and functions primarily as a chromatin reader regulating genes involved in cell-fate decisions. Here, we bred Brd4fl/fl Ox40-Cre mice in which Brd4 was conditionally deleted in OX40-expressing cells to examine the role of BRD4 in regulating immune responses. We found that the Brd4fl/fl Ox40-Cre mice developed profound alopecia and dermatitis, while other organs and tissues were not affected. Surprisingly, lineage-tracing experiments using the Rosa26fl/fl-Yfp mice identified a subset of hair follicle stem cells (HFSCs) that constitutively express OX40, and deletion of Brd4 specifically in such HFSCs resulted in cell death and a complete loss of skin hair growth. We also found that death of HFSCs triggered massive activation of the intradermal γδ T cells, which induced epidermal hyperplasia and dermatitis by producing the inflammatory cytokine IL-17. Interestingly, deletion of Brd4 in Foxp3+ Tregs, which also constitutively express OX40, compromised their suppressive functions, and this, in turn, contributed to the enhanced activation of γδ T cells, as well as the severity of dermatitis and hair follicle destruction. Thus, our data demonstrate an unexpected role of BRD4 in regulating skin follicle stem cells and skin inflammation.